Battery plug-in electric car : design and integration of battery packaging, bms, and associated systems - Shaman Suresh (2014)
In the last few decades, petroleum based vehicles have been deemed to cause much harm to the environment. The price of oil has also continued to increase and the amount of it left available is questionable. This outcry and uncertainty has thus led to a sharp rise in the research and development of electric vehicles. It is thus timely for NTU to venture into such a project which not only teaches students the basics of the automotive design process but also encourages students to develop an interest in electro-mobility. This project has entered its third year of development and so work was done to build on the progress of the previous students. The author was responsible for the design and integration of the battery pack as well as the battery management system. These two areas were heavy on electrical knowledge and the author thus had to do much research to gain a basic understanding before any progress could be made. The integration of the battery packs as well as the management system components will be addressed in this paper.